2014
DOI: 10.1016/j.crvasa.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Rescue venoarterial ECMO in cardiogenic shock complicated by refractory cardiac arrest during percutaneous coronary intervention

Abstract: Kardiogenní šok je hlavní příčinou úmrtí hospitalizovaných nemocných s akutními koronárními syndromy. V současnosti je jediným způsobem léčby s prokázaným přínosem okamžitá revaskularizace, a to buď perkutánní, nebo chirurgická. Přes nedostatek důkazů se k obnově hemodynamické stability -kromě revaskularizace -navíc běžně používá intraaortální balonková kontrapulsace (IABP) a podávají se vasoaktivní látky. Z hlediska hemodynamiky jsou kromě IABP k dispozici ještě účinnější zařízení pro mechanickou podporu oběh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“… 18 According to a previous study, cardiogenic shock patients might lead to a better survival rate due to early revascularization, especially using mechanical circulatory support devices to improve hemodynamic stability such as Impella, TandemHeart, and VA-ECLS. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 According to a previous study, cardiogenic shock patients might lead to a better survival rate due to early revascularization, especially using mechanical circulatory support devices to improve hemodynamic stability such as Impella, TandemHeart, and VA-ECLS. 19 …”
Section: Discussionmentioning
confidence: 99%
“…18 According to a previous study, cardiogenic shock patients might lead to a better survival rate due to early revascularization, especially using mechanical Kurniawati et al circulatory support devices to improve hemodynamic stability such as Impella, TandemHeart, and VA-ECLS. 19 Lactate and lactate clearance are viable parameters reflective of ECLS outcome. 20 It was demonstrated that high lactate levels are related to unfavorable prognoses, while rapid lactate clearance suggests adequate tissue reperfusion, increasing the likelihood of survival.…”
Section: Discussionmentioning
confidence: 99%
“…In such critical situations, we would use VA ECMO, which is an active technique, able to generate normal cardiac output and thereby completely replace the heart and lung [ 3 , 4 ]. Because of technical developments, the VA ECMO console has become smaller and priming may nowadays be safely performed by trained nurses in 5 to 10 min in the catheterization laboratory ( Figure 1 A ).…”
mentioning
confidence: 99%